2021
DOI: 10.1186/s12935-021-02151-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody-armed T cells endow CAR-T cells with cytotoxicity against lymphoma cells

Abstract: Background Taking advantage of nanobodies (Nbs) in immunotherapy, we investigated the cytotoxicity of Nb-based chimeric antigen receptor T cells (Nb CAR-T) against lymphoma cells. Methods CD19 Nb CAR-T, CD20 Nb CAR-T, and Bispecific Nb CAR-T cells were generated by panning anti-human CD19- and CD20-specific nanobody sequences from a natural Nb-expressing phage display library, integrating Nb genes with a lentiviral cassette that included other CAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…Our previous findings proved that nanobody based CAR-T cells possessed a highly efficient cytotoxicity to tumor cells, more notably, Bispecific Nb CAR-T cells (target CD19 and CD20 simultaneously) was more effective than single target. 60 Therefore, we further explore the killing efficiency of Nb CAR-T cells combined with spermidine. As mentioned, 5μM of spermidine treating brought remarkable cytotoxicity to CD19 CAR-T cells than 0.5μM, thus same dose was utilized to Nb CAR-T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous findings proved that nanobody based CAR-T cells possessed a highly efficient cytotoxicity to tumor cells, more notably, Bispecific Nb CAR-T cells (target CD19 and CD20 simultaneously) was more effective than single target. 60 Therefore, we further explore the killing efficiency of Nb CAR-T cells combined with spermidine. As mentioned, 5μM of spermidine treating brought remarkable cytotoxicity to CD19 CAR-T cells than 0.5μM, thus same dose was utilized to Nb CAR-T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, previously constructed Nb CAR-T cells were used to explore the effects of spermidine. 60 Previous results have shown that nanobody-based CAR-T cells can effectively activation (an activation marker) and proliferation when stimulated by Daudi cells, resulting in lysis of these tumor cells. It was worth mentioning that we found the positive rate had a significant impact on CAR-T cells anti-tumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…With the first US FDA‐approved nanobody monotherapy in 2019, considerably more effort has been invested in the feasibility of nanobody‐based CAR‐T therapy. Bispecific nanobody anti‐CD19+CD20 CAR‐T cells were constructed and killed B cell lines in vitro with high specificity and enhanced proliferation [ 168 ].…”
Section: Scfv and Nanobodies In Car‐t/nk Cellsmentioning
confidence: 99%
“…Multiple nanoCAR-T cell products are under preclinical investigation for diverse target antigens on both hematological malignancies as well as solid tumors (Table 5). Antigens that have been targeted with nanoCARs are: CD38 (1G3) , CD19 (Wang et al, 2021), CD20 (De Munter et al, 2018;Wang et al, 2021) andCD33 (De Munter et al, 2020) in hematological malignancies, and mucin-1 (AR32) (Bakhtiari et al, 2009;Iri-Sofla et al, 2011;Khaleghi et al, 2012), VEGFR2 (3VGR19) (Hajari and prostate-specific membrane antigen (PSMA) (NBP) (Hassani et al, 2019) in solid tumors. Targeting the tumor microenvironment (TME) instead of TAAs might provide a more generally applicable CAR therapy.…”
Section: Nanocars As Tools To Direct Cancer Cell Killingmentioning
confidence: 99%